"I Should Like to Point Out that There is an Air-Raid Going on Outside!": Psychoanalysis and the Denial of the Analyst's Trauma. Issue 1 (2nd January 2018) - Philipson, Ilene
Abstract : This paper examines the question of whether psychoanalysts today are as inured to their own traumatizing environments as were the members of the wartime British Society. Although trauma arguably is at the forefront of contemporary psychoanalytic thinking, it is always the trauma of the other about which we are concerned. It is argued that with the election of Donald Trump, therapists are as likely to feel as traumatized as many of their patients. Given the post–World War II consensus within American psychoanalysis that deemed the social and the political to be outside or beneath its purview, psychoanalysts may be particularly vulnerable to failing to acknowledge our own destabilization and vulnerability. If we do not find forms of containment and understanding of our suffering, for having to endure the daily onslaughts of the unimaginable while serving as support and containment for our patients, our work will become increasingly difficult, potentially both hurting ourselves and negatively impacting our patients.